Lactoferrin Levels in Breast Milk among Lactating Women of Low Socio-economic Status - Tabinda Taqi, Din Muhammad Shaikh, Navaid Qazi , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2013)
Objective: To assess the lactoferrin levels in breast milk among lactating women of low socio-economic status and to compare in different age groups for the same. Place and Duration: Prospective study conducted in the department of physiology, ISRA University Hyderabad, during June 2012 to Dec 2012. Patients and Methods: A total of 30 lactating mothers of low socio-economic status were involved in this study, divided into four age groups. The demographic data was compiled on a questionnaire proforma. The mother's consent was obtained before collection. 5-10 ml of breast milk was collected from each feeding mothers with breast pump into sterile bottle. The samples were transported on dry ice to the clinical laboratory for estimation ofthe lactoferrin levels using ELISA Method. Results: The majority 16 (53.3%) of cases were found in 21-30 years age group. The mean lactoferrin level detected in whole group was 2.47 mg/ml, the lowest mean lactoferrin level was detected in < 20 age group which was 1.81 mgiml and highest mean lactoferrin level was detected 2.76 mg/m1 in 21-30 years age group. The results of lactoferrin level were found significant in all age groups individually when analyzed statistically. Conclusion: The current study highlights the importance of health of lactating women in order to improve the quality of milk for their babies. The data collected & analysed shows significant difference in the lactoferrin levels of milk in lactating women of low socioeconomic population which is significantly correlates in different age.